Meaningful tourist transformations with Country at Bawaka, North East Arnhem Land, northern Australia. (December 2017) - Country, Bawaka; Wright, Sarah; Lloyd, Kate; Suchet-Pearson, Sandie; Burarrwanga, Laklak; Ganambarr, Ritjilili; Ganambarr, Merrkiyawuy; Ganambarr, Banbapuy; Maymuru, Djawundil; Tofa, Matalena
In this article, we discuss how human and more-than-human agencies, experienced and interpreted through emotions and sensory experiences, actively shape and enable transformative learning for tourists. We examine the narratives of two visitors to Bawaka Cultural Enterprises, an Indigenous-run tourism venture in North East Arnhem Land, northern Australia. We attend particularly to the more-than-human place of Bawaka and the ways the visitors are drawn into what is known as Bawaka Country. Indeed, transformation occurs as the visitors co-become with Country, become part of its ongoing co-constitution. We also examine the limits to transformations forged through such immersive tourism experiences. Ultimately, we suggest that for these visitors, more-than-human agencies create transformative learning experiences which build emotional and affective connections with people, places and causes. We argue that even though these connections may become diluted over time and distance, embodied and remembered experiences remain meaningful, having the potential to unsettle, connect and transform.